Immunization with different PfAMA1 alleles in sequence induces clonal imprint humoral responses that are similar to responses induced by the same alleles as a vaccine cocktail in rabbits - Kusi, Kwadwo A (BioMed Central, 2011)
BACKGROUND: Antibodies to key Plasmodium falciparum surface antigens have been shown to be important effectors that mediate clinical immunity to malaria. The cross-strain fraction of anti-malarial antibodies may however be required to achieve strain-transcending immunity. Such antibody responses against Plasmodium falciparum apical membrane antigen 1 (PfAMA1), a vaccine target molecule that is expressed in both liver and blood stages of the parasite, can be elicited through immunization with a mixture of allelic variants of the parasite molecule. Cross-strain antibodies are most likely elicited against epitopes that are shared by the allelic antigens in the vaccine cocktail. METHODS: A standard competition ELISA was used to address whether the antibody response can be further focused on shared epitopes by exclusively boosting these common determinants through immunization of rabbits with different PfAMA1 alleles in sequence. The in vitro parasite growth inhibition assay was used to further evaluate the functional effects of the broadened antibody response that is characteristic of multi-allele vaccine strategies. RESULTS: A mixed antigen immunization protocol elicited humoral responses that were functionally similar to those elicited by a sequential immunization protocol (p > 0.05). Sequential exposure to the different PfAMA1 allelic variants induced immunological recall of responses to previous alleles and yielded functional cross-strain antibodies that would be capable of optimal growth inhibition of variant parasites at high enough concentrations. CONCLUSIONS: These findings may have implications for the current understanding of the natural acquisition of clinical immunity to malaria as well as for rational vaccine design.